International Performance Research Pedagogies
XIX, 235 p.
Keywords: This book offers a unique and much-needed interrogation of the broader questions surrounding international performance research which are pertinent to the present and the future of Theatre and Performance studies. Marking the completion of eight years of the Erasmus Mundus MA Programme in International Performance Research (MAIPR) - a programme run jointly by the universities of Warwick (UK), Amsterdam (Netherlands), Helsinki/Tampere (Finland), Arts in Belgrade (Serbia), and Trinity College Dublin (Ireland) - the essays in this volume take stock of the achievements, insights and challenges of what international performance research is or ought to be about. By reflecting on the discipline of Performance Studies using the MAIPR programme as a case study in point, the volume addresses the broader question of the critical link between the discipline of Performance Studies and humanities education in general, examining their interactions in the contemporary university in the context of globalisation.